2017
DOI: 10.1002/2017gl073814
|View full text |Cite
|
Sign up to set email alerts
|

Variability and trends in surface seawater pCO2 and CO2 flux in the Pacific Ocean

Abstract: Variability and change in the ocean sink of anthropogenic carbon dioxide (CO2) have implications for future climate and ocean acidification. Measurements of surface seawater CO2 partial pressure (pCO2) and wind speed from moored platforms are used to calculate high‐resolution CO2 flux time series. Here we use the moored CO2 fluxes to examine variability and its drivers over a range of time scales at four locations in the Pacific Ocean. There are significant surface seawater pCO2, salinity, and wind speed trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 80 publications
6
67
5
Order By: Relevance
“…Wind speed is corrected to a height of 10 m above the sea surface using equation (1) of Sutton et al (). U10=Uz1+Cd100.4×ln()z10 where U 10 is wind speed in m/s at 10 m, z is the height (m) of the wind sensor, U z is wind speed in m/s recorded by the sensor, Cd 10 is the drag coefficient (0.0011), and 0.4 is von Karman constant.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Wind speed is corrected to a height of 10 m above the sea surface using equation (1) of Sutton et al (). U10=Uz1+Cd100.4×ln()z10 where U 10 is wind speed in m/s at 10 m, z is the height (m) of the wind sensor, U z is wind speed in m/s recorded by the sensor, Cd 10 is the drag coefficient (0.0011), and 0.4 is von Karman constant.…”
Section: Methods and Datamentioning
confidence: 99%
“…Wind speed is corrected to a height of 10 m above the sea surface using equation (1) of Sutton et al (2017).…”
Section: Height Correction Of Observed Wind Speedmentioning
confidence: 99%
“…Still, in 2015, there was a decline in zooplankton stocks off the coast of Mexico and a shift in the vertical distribution of fish larvae in response (Sánchez-Velasco et al, 2017). For the first time on record, the northeast Pacific Ocean was a pCO 2 source (Sutton et al, 2017) at the same time that net organic carbon production declined in 2015 (Figure 5a). Although the zooplankton stocks gradually recovered in 2015 (McKibben et al, 2017;McKinstry & Campbell, 2018), the consequences to fisheries came later.…”
Section: Environmental Consequences Of the 2013-2016 Warm Events And mentioning
confidence: 99%
“…The development of the Arc pattern along the west coast of United States between 2014 and 2015 altered the local phytoplankton community structure (Du & Peterson, 2018), with elevated SSTs stimulating harmful algae blooms in the northern California Current (McKibben et al, 2017;Zhu et al, 2017). For the first time on record, the northeast Pacific Ocean was a pCO 2 source (Sutton et al, 2017) at the same time that net organic carbon production declined in 2015 ( Figure 5a). For the first time on record, the northeast Pacific Ocean was a pCO 2 source (Sutton et al, 2017) at the same time that net organic carbon production declined in 2015 ( Figure 5a).…”
Section: Environmental Consequences Of the 2013-2016 Warm Events And mentioning
confidence: 99%
“…For example, long-term observations in a tropical coral reef system demonstrated the importance of various processes that influence air-sea CO 2 flux including rainfall, nutrient delivery, winds, and local biological communities [37,38]. Sustained mooring observations in the Tropical Pacific revealed that climate forcings such as El Niño/La Niña cycles [35,39] and anomalous warming events in the Pacific [40] are dominant drivers for interannual variability of pCO 2 . Furthermore, these surface observations of pCO 2 are compiled along with shipboard observations into the Surface Ocean CO 2 Atlas (SOCAT) [24], providing crucial information about the seasonal cycle for calculating global air-sea CO 2 fluxes (e.g., [41,42]).…”
Section: Surface Co 2 Measurementsmentioning
confidence: 99%